Probabilistic photonic computing for AI - Brückerhoff-Plückelmann, Frank; Ovvyan, Anna; Varri, Akhil; Borras, Hendrik; Klein, Bernhard; Meyer, Lennart; Wright, C. David; Bhaskaran, Harish; Syed, Ghazi Sarwat; Sebastian, Abu; Fröning, Holger; Pernice, Wolfram (Nature computational science, 2025)
Probabilistic computing excels in approximating combinatorial problems and modeling uncertainty. However, using conventional deterministic hardware for probabilistic models is challenging: (pseudo) random number generation introduces computational overhead and additional data shuffling. Therefore, there is a pressing need for different probabilistic computing architectures that achieve low latencies with reasonable energy consumption. Physical computing offers a promising solution, as these systems do not rely on an abstract deterministic representation of data but directly encode the information in physical quantities, enabling inherent probabilistic architectures utilizing entropy sources. Photonic computing is a prominent variant of physical computing due to the large available bandwidth, several orthogonal degrees of freedom for data encoding and optimal properties for in-memory computing and parallel data transfer. Here, we highlight key developments in physical photonic computing and photonic random number generation. We further provide insights into the realization of probabilistic photonic processors and their impact on artificial intelligence systems and future challenges.
Gesehen am 28.10.2025